2010
DOI: 10.1007/s00256-010-1067-1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of glomus tumors

Abstract: The diagnosis of glomus tumor is suggested by imaging features of a small circumscribed mass at the site of point tenderness that show marked vascularity on Doppler evaluation or diffuse contrast medium enhancement on MRI, or both. Early tumor recognition allows surgical resection that completely resolves the crippling, chronic pain of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
98
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(109 citation statements)
references
References 14 publications
4
98
1
6
Order By: Relevance
“…21 Marked vascularity of Doppler ultrasonographic evaluation has been described. 22 MR imaging has been described as the most sensitive modality, especially for smaller tumors. 22 A characteristic well-circumscribed T2 hyperintense lesion is most often found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Marked vascularity of Doppler ultrasonographic evaluation has been described. 22 MR imaging has been described as the most sensitive modality, especially for smaller tumors. 22 A characteristic well-circumscribed T2 hyperintense lesion is most often found.…”
Section: Discussionmentioning
confidence: 99%
“…22 MR imaging has been described as the most sensitive modality, especially for smaller tumors. 22 A characteristic well-circumscribed T2 hyperintense lesion is most often found. 22,23 Notably, the majority of published articles are in the form of case reports or small, retrospective case series.…”
Section: Discussionmentioning
confidence: 99%
“…Glomus tumors show increased signal intensity on T2 weighted images during high resolution MRI, thus being useful in identifying the tumor preoperatively and in evaluating its pathological process even in extradigital glomus tumors. However, it should be kept in mind that the possibility of a false negative result may arise when the tumor size is 2-3 mm [7]. …”
Section: Discussionmentioning
confidence: 99%
“…2,3 A recent study analyzed the imaging features of GTs in 25 cases: they are identified as wellcircumscribed, hypoechoic, highly vascularized masses on echography and color-Doppler evaluation and present with high T2 signal intensity and uniform enhancement after gadolinium administration at MRI. 4 Malignant features are extremely rare. [5][6][7][8][9][10][11][12][13][14][15][16][17] Malignant GTs, also known as glomangiosarcomas, seem to represent less than 1% of cases of GTs and occur mostly in nonacral sites.…”
Section: Discussionmentioning
confidence: 98%